Rhodococcus equi isolation from sputum of patients with suspected tuberculosis - Silva, Paulo da [UNESP]; Miyata, Marcelo; Sato, Daisy Nakamura; Santos, Adolfo Carlos Barreto [UNESP]; Mendes, Natália Helena [UNESP]; Leite, Clarice Queico Fujimura [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2010)
Rhodococcus equi has emerged as an opportunistic pathogen associated with pulmonary, invasive or systemic infections in immunocompromised patients. We report the identification of 51 R. equi isolates found in sputum samples of 546 individuals suspected to have pulmonary tuberculosis in two Public Health Hospital Units in Brazil. The epidemiology of R. equi infection as well as the phenotypic identification and drug susceptibility profile of isolates are described in this paper.
Keywords: Rhodococcus equi; identification; tuberculosis; antimicrobial profile; epidemiology